A novel dinucleotide variant at 5′ splice sites in the F8 gene causes exon 19 skipping in a Chinese family with hemophilia A - Zhou, Xunzhao; Yang, Qi; Chen, Qiuli; Yi, Sheng; Wei, Shengkai; Luo, Jingsi; Meng, Dahua; Qin, Zailong; Zhang, Shujie (Frontiers in Genetics, 2025)
BackgroundHemophilia A is a rare, severe X-linked recessive inherited hemorrhagic disorder caused by F8 gene dysfunction, which is characterized by spontaneous or post-traumatic bleeding tendencies. The pathogenic variants identified in the F8 gene contribute to prenatal diagnosis and genetic counseling services for patients and their families.MethodsWe used inverse shifting-PCR (IS-PCR), direct DNA sequencing, bioinformatics predictions, cDNA sequencing, and minigene splicing assays to explore candidate variants in a Chinese family with hemophilia A. The identified variant was classified in accordance with ACMG/AMP guidelines.ResultsA novel c.6115+5_6115+6delinsAG variant at 5′ splice sites (5’ss) in exon 19 was identified in a 14-year-old Chinese boy with hemophilia A by DNA sequencing, which is inherited from his asymptomatic carrier mother. Multiple bioinformatics prediction tools, including SD-Score, information content (Ri), varSEAK, and RDDC RNA splicer, predicted that this variant might affect the normal pre-mRNA splicing. Both cDNA sequencing and minigene splicing assays proved that the variant led to exon 19 skipping in the F8 gene, which was ultimately classified as pathogenic according to the ACMG/AMP guidelines.ConclusionThe c.6115+5_6115+6delinsAG variant in the F8 gene is considered to be responsible for hemophilia A in this family. This dinucleotide variant located at 5’ss of the gene is initially reported. Our study has expanded the mutation spectrum of F8 and provided a basis for prenatal and clinical diagnosis.